A Novel, Enriched Population Pharmacokinetic Model for Recombinant Factor VIII-Fc Fusion Protein Concentrate in Hemophilia A Patients - Bukkems, Laura H.; Heijdra, Jessica M.; Mathias, Mary; Collins, Peter W.; Hay, Charles R. M.; Tait, Robert C.; Mangles, Sarah; Myers, Bethan; Evans, G.; Bailiff, Benjamin; Curry, Nicola; Payne, Jeanette; Austin, Steve; Goedhart, Tine M. H. J.; Leebeek, Frank W. G.; Meijer, Karina; Fijnvandraat, Karin; Chowdary, Pratima; Mathôt, Ron A. A.; Cnossen, Marjon H.; for UK-EHL Outcomes Registry OPTI-CLOT Collaboration (Thrombosis and Haemostasis, 2020)
Background The currently published population pharmacokinetic (PK) models used for PK-guided dosing in hemophilia patients are based on clinical trial data and usually not externally validated in clinical practice. The aim of this study was to validate a published model for recombinant factor VIII-Fc fusion protein (rFVIII-Fc) concentrate and to develop an enriched model using independently collected clinical data if required.Methods Clinical data from hemophilia A patients treated with rFVIII-Fc concentrate (Elocta) participating in the United Kingdom Extended Half-Life Outcomes Registry were collected. The predictive performance of the published model was assessed using mean percentage error (bias) and mean absolute percentage error (inaccuracy). An extended population PK model was developed using nonlinear mixed-effects modeling (NONMEM).Results A total of 43 hemophilia A patients (FVIII ≤ 2 IU/dL), aged 5 to 70 years, were included. The prior model was able to predict the collected 244 rFVIII-Fc levels without significant bias (–1.0%, 95% CI: –9.4 to 7.3%) and with acceptable accuracy (12.9%). However, clearance and central distribution volume were under predicted in patients <12 years, which was expected as this age group was not represented in the previous model population. An enriched population PK model was constructed, which was able to successfully characterize PK profiles of younger children.Conclusion We concluded that the existing rFVIII-Fc population PK model is valid for patients ≥ 12 years. However, it is not reliable in younger patients. Our alternative model, constructed from real world patient data including children, allows for better description of patients ≥5 years.
Keywords: recombinant factor VIII-Fc; population; pharmacokinetics; child; validation